The Importance of Keeping Pesticide Records - Frederick M. Fishel (EDIS)
Keeping accurate records of pesticide use makes good sense. In some cases, you are required by law to maintain records on pesticide use but having records available can also help you improve your operation. This 8-page fact sheet outlines who is required to keep records of pesticide use and the appropriate contents. Written by F. M. Fishel, and published by the UF Department of Agronomy, May 2013.